The uses of ICT in the commodification of the university: An analysis of the EHEA official documents - Ballesteros Carrasco, Begoña; Franco Romo, Daniel; Pedro Carañana, Joan (Estudios sobre el Mensaje Periodístico, 2012)
The construction of the European Higher Education Area (EHEA) is profoundly transforming the university. Changes underway orient the university institution toward a model in which economic profitability and private utilization of knowledge wield a greater role. Information and Communication Technologies (ICT) play a strategic role in this process. By analyzing the documents that define the project of the EHEA, the article discusses the uses of ICT being promoted by official institutions to contribute to the ongoing transformation of the university.
Keywords: capitalism; commodification; ICT; university